Smoking Czechs: Modeling tobacco consumption and taxation - Karel Janda; Martin Strobl (Charles University in Prague, Institute of Economic Studies (IES), 2018)
We model the future tobacco consumption, size of smoking population and governmental tax revenues in the Czech Republic. The main assumption of our model states that smokers determine their future tobacco consumption behavior as adolescents. Further assumptions make the model applicable to the data from the Czech National Monitoring Centre for Drugs and Drug Addiction. Future teenage smoking rates and average consumption are the inputs to the model; consumption growth coeffcients for each age category are estimated using zero-inflated negative binomial regression. Several scenarios are built to model possible developments, including extreme cases. All our scenarios show that all model outcomes are going to grow until 2028 in a very similar pattern. In particular, the projected number of smokers in 2028 is by 4-8% higher than in 2013, the total daily tobacco consumption and tax revenue by 7-26%. This increase is induced by aging of large birth cohorts.
Keywords: D12; I12; 330; smoking; tobacco; cigarettes; consumption; taxation; forecasting